2019
DOI: 10.3390/pathogens8040161
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Correlates of Short Term Virologic Response among Treatment-Naïve HIV-Infected Children Initiating Antiretroviral Therapy in Ethiopia: A Multi-Center Prospective Cohort Study

Abstract: There is limited data on virologic outcome and its correlates among HIV-infected children in resource-limited settings. We investigated rate and correlates of virologic outcome among treatment naïve HIV-infected Ethiopian children initiating cART, and were followed prospectively at baseline, 8, 12, 24 and 48 weeks using plasma viral load, clinical examination, laboratory tests and pretreatment HIV drug resistance (PDR) screening. Virologic outcome was assessed using two endpoints–virological suppression define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…This result could be explained by the predominance of the age groups 6 to 9 years (in children) and 10 to 15 years (in adolescents). Our results are similar to those of a study conducted by Fokam et al at the Health Centre of the National Social Security Fund in Yaoundé, Cameroon, which found a median (IQR) age of 13 (11–16) years among adolescents, and the study conducted by Tadesse et al in Ethiopia, who found a median age of 9 (5–12) years among the population aged 3 to 12 years [ 8 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result could be explained by the predominance of the age groups 6 to 9 years (in children) and 10 to 15 years (in adolescents). Our results are similar to those of a study conducted by Fokam et al at the Health Centre of the National Social Security Fund in Yaoundé, Cameroon, which found a median (IQR) age of 13 (11–16) years among adolescents, and the study conducted by Tadesse et al in Ethiopia, who found a median age of 9 (5–12) years among the population aged 3 to 12 years [ 8 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Of note, suboptimal adherence to treatment is known as a major determinant of ART failure among children in Cameroon [ 16 ]. In effect, a suboptimal adherence level is a major challenge often reported in children and adolescents due to a lack of psychological support and close monitoring by tutors and clinicians [ 12 , 13 , 14 , 15 , 16 , 17 , 19 ]. In our present study, adherence was measured by self-reporting, which is a method with possible recall bias from clients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, children were far from the UNAIDS 90-90-90 goals, were not getting optimum treatment, and had lower rates of viral suppression than adults [1, 3,4]. Recently we reported poor viral suppression [5,6], high rates of viral drug resistance [7,8], and treatment-associated adverse events [9,10] among HIV-infected Ethiopian children.…”
Section: Introductionmentioning
confidence: 99%
“…Two (8%) studies were comparative RCTs 13,20 and one (4%) was a singlearm, phase 2 trial 21 with abacavir used as backbone. 12 (50%) were prospective cohort studies, 15,[22][23][24][25][26][27][28][29][30][31][32] including one cohort nested in an RCT. 22 Seven (29%) were retrospective cohort studies 14,[33][34][35][36][37][38] and two (8%) were crosssectional surveys.…”
Section: Resultsmentioning
confidence: 99%